(untitled) (Journal of Economic Additions, 2025)
This study examined the legal framework of Takaful insurance in Algeria, which was authorized by Article 103 of Law No. 19-14 (Finance Law of 2020), though its operational details were clarified only after Decree No. 21-81. It also assessed the current state of Takaful through Algeria Takaful Company and Algeria United Company. The study found that Takaful insurance in Algeria faces challenges such as limited technical and legal expertise, and the absence of appropriate accounting and tax systems. It recommends adopting digital technologies to expand access. Keywords: Takaful insurance; commercial insurance; Decree No. 21-81; Algeria Takaful; Algeria United. Jel Classification Codes: D53, D86.